PENGARUH MEDIA DOMINO HITUNG TERHADAP HASIL BELAJAR DAN MINAT SISWA - Siska Pratiwi; Abdussalam; Yunita Hariyani; Ihwan Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning outcomes and interests of class IC students are classified as low/minimal because teachers rarely use learning media and students appear inactive during learning. The purpose of this study was to determine the effect of domino counting media on learning outcomes and student interests. The type of research and research design used were quantitative and one group pretest posttest design. Data collection techniques used were tests and questionnaires. Data analysis techniques used were validity tests, reliability tests, normality tests, paired sample t tests, and manova tests. The results of the manova test obtained a significance value <0.05, so it can be concluded that there is an effect of domino counting media on learning outcomes and student interests.